Carvedilol Phenocopies PGC-1α Overexpression to Alleviate Oxidative Stress, Mitochondrial Dysfunction and Prevent Doxorubicin-Induced Toxicity in Human iPSC-Derived Cardiomyocytes - Nnamdi Uche; Qiang Dai; Shuping Lai; Kurt Kolander; Mai Thao; Elizabeth Schibly; Xavier Sendaydiego; Jacek Zielonka; Ivor J. Benjamin (MDPI AG, 2023)
Doxorubicin (DOX), one of the most effective and widely used anticancer drugs, has the major limitation of cancer treatment-related cardiotoxicity (CTRTOX) in the clinic. Reactive oxygen species (ROS) generation and mitochondrial dysfunction are well-known consequences of DOX-induced injury to cardiomyocytes. This study aimed to explore the mitochondrial functional consequences and associated mechanisms of pretreatment with carvedilol, a ß-blocking agent known to exert protection against DOX toxicity. When disease modeling was performed using cultured rat cardiac muscle cells (H9c2 cells) and human iPSC-derived cardiomyocytes (iPSC-CMs), we found that prophylactic carvedilol mitigated not only the DOX-induced suppression of mitochondrial function but that the mitochondrial functional readout of carvedilol-pretreated cells mimicked the readout of cells overexpressing the major regulator of mitochondrial biogenesis, PGC-1α. Carvedilol pretreatment reduces mitochondrial oxidants, decreases cell death in both H9c2 cells and human iPSC-CM and maintains the cellular 'redox poise' as determined by sustained expression of the redox sensor Keap1 and prevention of DOX-induced Nrf2 nuclear translocation. These results indicate that, in addition to the already known ROS-scavenging effects, carvedilol has a hitherto unrecognized pro-reducing property against the oxidizing conditions induced by DOX treatment, the sequalae of DOX-induced mitochondrial dysfunction and compromised cell viability. The novel findings of our preclinical studies suggest future trial design of carvedilol prophylaxis, such as prescreening for redox state, might be an alternative strategy for preventing oxidative stress writ large in lieu of the current lack of clinical evidence for ROS-scavenging agents.